Do user preferences align with human factors assessment scores of drug–drug interaction alerts?. (March 2020) - Lowenstein, David; Zheng, Wu Yi; Burke, Rosemary; Kenny, Eliza; Sandhu, Anmol; Makeham, Meredith; Westbrook, Johanna; Day, Richard O; Baysari, Melissa T
This study aimed to assess drug–drug interaction alert interfaces and to examine the relationship between compliance with human factors principles and user-preferences of alerts. Three reviewers independently evaluated drug–drug interaction alert interfaces in seven electronic systems using the Instrument-for-Evaluating-Human-Factors-Principles-in-Medication-Related-Decision-Support-Alerts (I-MeDeSA). Fifty-three doctors and pharmacists completed a survey to rate the alert interfaces from best to worst and reported on liked and disliked features. Human factors compliance and user-preferences of alerts were compared. Statistical analysis revealed no significant association between I-MeDeSA scores and user-preferences. However, the strengths and weaknesses of drug–drug interaction alerts from users' perspectives were in-line with the human factors constructs evaluated by the I-MeDeSA. I-MeDeSA in its current form, is unable to identify alerts that are preferred by the users. The design principles assessed by I-MeDeSA appear to be sound, but its arbitrary allocation of points to each human factors construct may not reflect the relative importance that the end-users place on different aspects of alert design.